Brasil e Argentina: política externa do Estado Novo e o projeto desenvolvimentista - Pavanelli, Thiago Augusto Malvestio (2014)
The international policy of the New State was characterized, among other things, by the existence of a developmental project. This project would only be possible with the acquisition of external technologies and capital. The Second World War was the ideal time to put into practice this policy, precisely because of the dispute between the countries, which made arrangements to get allies. Brazil, after remaining neutral at the beginning of the conflict - in order to get the most out of the dispute between the United States and Germany - found himself allied with the United States, thereby decreasing the Brazilian maneuvers. However, with Argentina increasingly moving away from the Americans, the political importance of Brazil further increased. The aim of this paper is to show how political developments in Argentina favored Brazil in an attempt to put into practice their developmental project. Will be taken an analysis of three events that precisely targeted the development of the country, these being the creation of the National Steel Company; strengthening of the Armed Forces, and the creation of the Brazilian Expeditionary Force, comparing the events in Argentina with success in the negotiations on these facts